Novas espécies de Eudorylas Aczél da estação ecológica de Maracá, Roraima, Brasil (Diptera: Pipunculidae) Eudorylas Aczél new species from the Maracá Ecological Station, Roraima, Brazil (Diptera: Pipunculidae) - José Albertino Rafael; Maria do Socorro dos Santos Rosa (Memorias do Instituto Oswaldo Cruz, 1989)
Five new species Eudorylas Aczél are described from Maracá Ecological Station, Roraima, Brazil, namely: E. aquinoi, E. bentoni, E. caccabatus, E. megasurstylus and E. souzalopesi.